Medicplast - a novel and green biodegradable medical plastic bag - Noor Wirda Aryanie, Mohd Zaki; Rohani, Arbain; Sam, Sung Ting, Dr.; Nik Noriman, Zulkepli, Dr. (Universiti Sains Malaysia, 2013)
Nor Wirda Aryanie and her team has won silver medal at National Research and Innovation Competition (NRIC) 2012, 17th - 19th July 2012 held at Dewan Utama Pelajar, located at USM Main Campus, Penang, Malaysia.